Development of Problem Based Learning (PBL) Learning Module on Chemical Bonding Material - Simbolon, Nasio Ruth Lusianna; Br. Simbolon, Endang Ristauli; Panggabean, Indah Tripena; Sihotang, Partogi Mahatma; Simanullang, Romian Afrina (Jurnal Pendidikan dan Pembelajaran Kimia, 2024)
Limited teaching materials are often a problem in learning in schools. A module is a specific form of teaching material that aims to guide students in understanding a particular material independently. This study aims to determine the feasibility, student responses and effectiveness of the Problem Based Learning (PBL) learning module on chemical bonding material that has been developed. The research method is Research and Development (R&D) using a 4D model that is limited to 3D with stages namely define, design, development due to limited time. Data collection in this study was through interviews, questionnaires and through pre-tests and post-tests. The results showed that the learning module developed had a very good level of validity with percentage scores: 91.66% and 93.75% for the presentation aspect, 95% for the language aspect, 93.75% for the content aspect, 91.66% for the e-module design aspect, and 95% for the material aspect. This electronic-based learning module is declared very valid and suitable for use as teaching material in chemistry learning on chemical bonding material.Keywords: Learning Module, Problem Based Learning, Development, Chemical Bonding, and R&D Method.DOI: 10.23960/jppk.v13.i3.32677